Histomorphometric and immunohistochemical assessment of treated dentin matrix delivered by platelet-rich fibrin for socket preservation in rabbit model - Eman M. Sedek; Nesma Mohamed Khalil; Mohamed M. Abdul-Monem (BMC Oral Health)
Abstract Objectives This study aimed to test treated dentine matrix (TDM) with platelet-rich fibrin (PRF) for socket preservation, following tooth extraction compared to synthetic grafting material Nanobone (NB) with PRF. Materials and methods Study was conducted on New Zealand rabbits (n = 40). Bilateral first lower premolar extraction was performed, with one side left empty and the other side filled with (PRF) in one group (n = 20). In the other group (n = 20), one side was filled with TDM/PRF while the other side was filled with NB/ PRF. After one and three months, rabbits were euthanized, and the socket area was examined using haematoxylin and eosin (H&E) and Goldner Masson trichrome stains. One-way ANOVA and post-hoc tests were used for histomorphometric analysis. Immunohistochemical analysis of osteopontin was carried out. Results Histological analysis of NB/PRF and TDM/PRF groups showed a higher level of new bone formation in comparison to the control and PRF groups. Histomorphometric analysis revealed a significant increase in new bone formation in the TDM/PRF group compared to the NB/PRF group after one and three months (p = 0.042 and p < 0.001), respectively. There were no significant differences in the percentages of unmineralized bone between the TDM/PRF and NB/PRF groups at both intervals (p = 0.375 and 0.352, respectively). Regarding immunohistochemistry, NB/PRF showed the highest osteopontin immune expression followed by TDM/PRF. No significant differences were detected between both groups at both intervals (p = 0.234 & 0.607 respectively). Conclusions TDM/PRF showed the ability to form new bone in extraction sockets in rabbits. Clinical relevance TDM/PRF can be used as an alveolar bone grafting material for socket preservation.